Enhancement of bile resistance in Lactobacillus plantarum strains by soy lecithin. (1st July 2015) - Hu, B.; Tian, F.; Wang, G.; Zhang, Q.; Zhao, J.; Zhang, H.; Chen, W.
Abstract: This study evaluated the effect of soy lecithin on the bile resistance of Lactobacillus plantarum . Six strains were cultured in MRS broth supplemented with soy lecithin at different concentrations. The strains incubated in MRS broth with 1·0% soy lecithin showed no inhibitory effect on cell growth. After culturing in MRS broth with 0·2–1·0% soy lecithin, the survival rate of harvested cells increased significantly ( P < 0·05) in the 0·3% bile challenge compared with the no added soy lecithin group. The cells incubated with 0·6% soy lecithin were able to grow in an MRS broth with a higher bile salt content. The surface hydrophobicity and cell leakage in the bile challenge were assessed to reveal the physical changes caused by the addition of soy lecithin. The cell surface hydrophobicity was enhanced and the membrane integrity in the bile challenge increased after culturing with soy lecithin. A shift in the fatty acid composition was also observed, illustrating the cell membrane change in the soy lecithin culture. Significance and Impact of the Study: In this study, we report for the first time the beneficial effect of adding soy lecithin to an MRS broth on subsequent bile tolerance of Lactobacillus plantarum . Soy lecithin had no inhibitory effect on strain viability but significantly enhanced bile resistance. Surface hydrophobicity and cell integrity increased in strains cultured with soy lecithin. The observed shift in the cell fatty acid composition indicated changes to the cell membrane. As soy lecithin is safe for use in the food industry, its protective effects can be harnessed for the development of bile‐sensitive strains with health‐benefit functions for use in probiotic products.